Analyzing the Concept of Spatial Transformation through the Example of Selimiye Bath - Atik, Zeynep; Demircioğlu, Ayşe İpek (Journal of Interior Design and Academy, 2024)
Baths are places that have survived to the present day as proof of cleanliness throughout history. The impact of the baths seen in civilizations has diminished with the use of bathrooms in houses, and has been transformed by losing its spatial function with urbanization. In this direction, the article examines the development of baths in terms of wet spaces with a chronological classification and analyzes the sections of Selimiye Bath, an Ottoman bath, before spatial transformation (undressing, warmth, warmth, ashtray) and after spatial transformation (food and beverage space) with on-site observation method. With the visual data obtained with this method, for the place that started to serve under the name Nevmekan Selimiye after the spatial transformation; historical texture, material, color, etc. It can be said that it is a successful spatial transformation study by functioning with functions related to the space without breaking its atmosphere with elements such as.